Stowaways - Brezenoff, Steven (Brezenoff, Steven. Return to Titanic, 2012)
When a teacup from the special collection of Titanic artifacts transports Tucker and Maya back to the day the Titanic sank, they set out to find their new friend Liam and his family--can they convince the captain to change the ship's course and rewrite history before the ship hits the iceberg?